STRATEGIC INITIATIVES ON UNIVERSAL HEALTH COVERAGE PROGRAM’S PERFORMANCE IN KENYA - OGWENGO, KENNEDY ONGOYE (Kabarak University, 2024)
Universal Health Coverage (UHC) in an economy is a critical component of sustainable development and poverty reduction and a key element of any effort to reduce social inequalities (Kodali, 2023). Kenya’s UHC was anchored in its Health Policy 2014-2030. The policy implementation process adopted a multisectoral approach involving different stakeholders at the national and county levels, regulatory bodies and service providers; and non-state actors who included professional associations, health workers unions, civil society organizations, health providers as well as health insurers; and development partners. The piloting of UHC was subsequently undertaken in 4 counties; Kisumu, Nyeri, Isiolo and Machakos from December 2018 until it was abandoned with the introduction of the new Universal Health Care plan of 2023. Although it was intended to ensure that all Kenyans accessed and received essential health services without financial hardships, its success was unclear. The study, therefore, endeavored to determine the effects of selected strategic initiatives that were undertaken during the UHC's piloting on the expected performance outcomes of the program. Specific objectives were to determine the effect of Health research and development initiatives, Health policy and planning initiatives, National health strategic plans monitoring, and Sustainable health financing initiatives. The research was anchored on the Conflict Theory, Theory of Strategic Balancing, Institutional Theory, and Resource Based Theory. It adopted the explanatory research design in an attempt to explain how the strategic initiatives affected the program performance. The target population for this study comprised 744 management members of healthcare organizations obtained from a sampling frame with the Director of Medical Services office. Data for each institution was collected from appointed organizational senior management representatives with a sample size of 260 respondents obtained using stratified sampling technique. Data was collected through semi-structured questionnaires and analyzed using descriptive statistics and inferential statistics, which included Pearson product-moment correlation and multiple linear regression analysis. The study found that research and development strategy initiatives (r = 0.374; p = 0.000), Health policy (r = 0.122, p= 0.038), Health Strategic Plan (r = 0.334, p = 0.000), Sustainable health financing (r = 0.267; p = 0.000) significantly influenced the performance of UHC pilot program. Environmental dynamism was found to significantly moderate the relationship between the strategic initiatives and the performance of UHC (R2 change = 0.174, p = 0.000). The study, therefore, concluded that the strategic initiatives significantly affected the performance of UHC in Kenya, however, they were negatively affected by environmental dynamism variables Policy change and Financing models but positively affected by health Strategic Planning.Therefore, the study recommends that healthcare organizations should engage in more research and development activities to enable them overcome barriers to the implementation of UHC. There is need for improved resource allocation and deployment of support systems to support policy implementation in UHC. Further, UHC policymakers and implementers need to consider a range of sustainable health financing schemes that have high penetration rates and low volatility to achieve higher coverage. Finally, there is a need to create mechanisms to ensure stable policy implementation in the face of environmental dynamism.
Keywords: Initiatives; Research; Dynamism; Policy; Planning; Sustainabl; Financing